ENGLISH TEACHER PROFESSIONAL DEVELOPMENT:A Case Study of Three Junior High School English Teachers in Pidie Regency, NAD - Warahmah, Mawaddah (2009)
This study is concerned with English teacher professional development. It aimed to investigate English teacher professional development (TPD) including the activities conducted by the teachers in developing their professionalism, the characteristics of good language teachers developed during the TPD activities and the implementation of the characteristics in the teaching performance. This study used a case study research design involving three Junior High School English teachers in Pidie Regency in Nanggroe Aceh Darussalam. The data were collected through questionnaire, interview, document analysis, and observation. Questionnaire, interview and document analysis were used to explore the activities conducted by the teachers in developing their professionalism and the characteristics developed through the TPD activities. Classroom observation was conducted to gain data concerning the implementation of the characteristics in the teaching performance. The data collected were analyzed using qualitative method. Regarding the first research problem, it is found that the three participants conducted/participated in some activities of English teacher professional development. The activities were self-reflection (Richards & Lockhart, 1994), classroom action research, cooperative development, peer teaching/peer observation, teachers' group/ teachers' association (MGMP), seminars, workshops, and trainings, professional literature, and broader view of TPD activities (see Harmer, 2001). However, classroom action research was rarely conducted. In this case, only one teacher conducted the activity. Among the TPD activities proposed by Harmer (2001), virtual community was the only one which was not conducted by the teachers. It was found that the main factors influencing teacher professional development were lack of time and lack of school facilities. Moreover, self-reflection, teachers' association (MGMP), and teachers' trainings were believed to be the most useful programs. Teachers' trainings were also believed to be the program which really supported them to be certified teachers. Concerning the second research problem, it is found that in general, there were many characteristics of a good language teacher (see Brown, 2001) developed through each activity. Moreover, there were four characteristics which were the most developed, i.e. "understands the linguistic system of English phonology, grammar, and discourse", "knows through experience what it is like to learn a foreign language", "understands the close connection between language and culture", and "maintains and exemplifies high ethical and moral standards". The least developed characteristic is "sets short-term and long-term goals for continued professional growth". For the third research problem, this study found that in general, the teachers showed positive effort in implementing the characteristics in four areas of teachers' skills. They are technical knowledge, pedagogical skills, interpersonal skills, and personal qualities. However, some characteristics were still weakly implemented. In addition, some implementations of the pedagogical skills were not evidenced during the observation such as "creatively adapts audio, visual and mechanical aids" and "innovatively creates brand new material when needed".